Intrasystem Shift Analysis In The Maze Runner Novel By Yunita Candra - Kur'Anna, Vita, Dr. Dwi Haryanti, M.Hum (2017)
ABSTRACT This research is descriptive qualitative study concerning of intra-system shift. The research purposes are to classify the intra-system shift in English-Indonesia novel The Maze Runner and to describe the quality of the translation of the novel. The data of this research is phrase, clause and all sentences containing the intra-system shift and their translation. The data source are novel The Maze Runner English version and also Indonesia version. The researcher uses documentation, questioner and interviewing as the method of collecting data for this research. The result of this study shows that there are 5 types of intra-system shift. They are 1) 18.8% data of noun plural translated into noun singular 2) 0.9% data of noun singular translated into noun plural 3) 59.4% data of verb-ed translated into verb 4) 16% data of verb-ing translated into verb 5) 4.6% data of verb-s/-es translated into verb. And then the quality of the translation, they are 1) Accuracy that are divided into 2, accurate 988 data or 92.3%, less accurate 82 data or 7.6%, 2) Acceptability that are divided into 2, they are acceptable 1050 or 97% data and less acceptable 20 data or 3%, 3) Readability that was divided into 2, high readability 1070 data or 100% and medium readability 0%. Keyword: intra-system shift, translation shift, quality